FRAGMENTATION STUDIES OF D6,7-ANHIDROERITROMISIN-A BY LIQUID CHROMATOGRAPHY-MASS SPECTROSCOPY (LC-MS) - Khairan Khairan; Umar A. Jenie; Retno S. Sudibyo (Indonesian Journal of Chemistry, 2009)
Semisynthesis of D6,7-Anhydroerythromycin-A was done by biomodification technique by addition of 0.2% INH into a culture fermentation of Saccharopolyspora erythraea ATCC 11635 in medium Hutchinson. The aim of this research is to studies of fragmentation pattern from new matabolite of D6,7-Anhydroerythromycin-A by Liquid Chromatography-Mass Spectroscopy (LC-MS) and the ionization of mass spectroscopy is use by ESI (Electrospray Ionization) pattern. The FT-IR spectrometric analyzes showed a stretching vibration of C=C conjugated group at wave number 1602.7 cm-1. This C=C conjugated vibration indicated the existence of double bond between C6 and C7 (D6,7), this confirmed that isolate contained D6,7-Anhydroerythromycin-A (the possibility of D6,7 was positive). For complementation, a LC-MS (Liquid Chromatography-Mass Spectroscopy) analyzes using ESI-MS (Electrospray Ionization-Mass Spectroscopy) ionization pattern was conducted to the isolate which resulted Quassimolecular ions [M+H]+ of D7,8- and D6,7-Anhydroerythromycin-A. LC-MS spectrogram of the isolate, which gave two peaks of m/z 732.2460 and m/z 716.2522, confirmed that the m/z 732.2460 possibly was D7,8-Anhydroerythromycin-A, while the m/z 716.2502 and m/z 715.2522 possibly were D6,7-Anhydroerythromycin-A.